PENGARUH PSYCHOLOGICAL ATTACHMENT DALAM PENGGUNAAN SISTEM INFORMASI - Rahmawaty, Anita (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2014)
This research investigates the effect of psychological attachment on the information system usage behaviors. This research is different from previous studies by integrating the variable of psychological attachment (internalization, identification and compliance) with Technology Acceptance Model (TAM). There are eight variables in this study, namely the perceived usefulness, perceived ease of use, psychological attachment (internalization, identification and compliance), attitude toward using, behavioral intention and actual use.This research is a type of survey research by using a quantitative approach. The research data are obtained from 117 students in Yogyakarta, by using random sampling technique. For research model testing technique, it used the multiple linear regression approach. The research's findings include three items. First, perceived ease of use, identification and compliance are positively and significantly effect on attitude toward using. Second, attitude toward using, identification and compliance are positively and significantly effect on behavioral intention. Third, behavioral intention is positively and significantly effect on information system usage behaviors. Finally, the research findings suggested that psychological attachment (identification and compliance) are the important variables that effect on information system usage behaviors.Keywords: Psychological attachment, technology acceptance model, information system.Penelitian ini menganalisis pengaruh psychological attachment terhadap perilaku penggunaan sistem informasi. Penelitian ini berbeda dengan riset terdahulu dengan mengintegrasikan variabel psychological attachment (internalization, identification dan compliance) dengan Technology Acceptance Model (TAM). Terdapat 8 variabel dalam penelitian ini, yaitu perceived usefulness, perceived ease of use, psychological attachment (internalization, identification dan compliance), attitude toward using, behavioral intention dan actual use.Penelitian ini merupakan penelitian survey dengan menggunakan pendekatan kuantitatif. Data penelitian dikumpulkan dari sebanyak 117 mahasiswa di Yogyakarta dengan menggunakan teknik simple random sampling. Sementara itu, teknik analisis datanya menggunakan uji regresi linier berganda.Temuan penelitian ini menunjukkan bahwa: 1) perceived ease of use, identification dan compliance berpengaruh secara positif dan signifikan terhadap sikap; (2) attitude toward using, identification dan compliance berpengaruh secara positif dan signifikan terhadap minat perilaku; (3) Minat perilaku berpengaruh secara positif dan signifikan terhadap perilaku penggunaan sistem informasi. Dengan demikian, temuan penelitian ini menunjukkan bahwa psychological attachment (identification dan compliance) merupakan variabel penting yang mempengaruhi perilaku penggunaan sistem informasi.Kata Kunci : Psychological attachment, technology acceptance model, sistem informasi.